NILAI-NILAI PENDIDIKAN ISLAM DALAM UPACARA PANGGIH PENGANTEN BANYUMASAN - Septiyani Dwi Kurniasih (Jurnal Penelitian Agama, 2018)
Abstract: This research is motivated by the development of the era and technology which has an impact on the number of western cultures that have entered Indonesia. These cultures have shifted the position of local culture in the community. Likewise with Javanese culture which is increasingly not understood by the wider community, especially the Javanese themselves. Though many lessons and noble values ​​of Javanese culture such as at the wedding ceremony. Another case in people's lives in Banjarparakan Village, Rawalo District, Banyumas Regency. In the village, there are still many people who preserve Javanese culture, especially at weddings. The community runs a wedding ceremony for their children as a cultural preservation effort that has noble values. The Banjarparakan Village Community also believes that by preserving Javanese culture, especially in wedding ceremonies, it will manifest a virtuous and moral society. The focus of this research is the bride-to-bride ceremony and the values ​​of Islamic education in the Banyumasan bride-to-bride ceremony. Keywords: Islamic Education Values. Sophisticated bride.